Ahli Waris Pengganti Di Tinjau Dari Kuhperdata Dan Kompilasi Hukum Islam - Sekar Dita Utari; Diangsa Wagian; Fatria Hikmatiar Al Qindy (Private Law, 2023)
This study aims to examine the position and system of distribution of substitute heirs under the Civil Code and Islamic Law Compilation (KHI). This research adopts a normative research approach. The results of this study indicate that the position of substitute heirs under the Civil Code occurs when an heir predeceases the testator, resulting in the children of the deceased heir replacing their father's position to inherit the ancestral property and receive a share of the inheritance according to their degree of relationship and rightful portion. On the other hand, according to the KHI, the position of substitute heirs is applicable to grandchildren who are entitled to replace their predeceased parents. However, their share is not equal to that of their parents.